2014
DOI: 10.1007/s10822-014-9714-6
|View full text |Cite
|
Sign up to set email alerts
|

The SAMPL4 hydration challenge: evaluation of partial charge sets with explicit-water molecular dynamics simulations

Abstract: We used blind predictions of the 47 hydration free energies in the SAMPL4 challenge to test multiple partial charges models in the context of explicit solvent free energy simulations with the GAFF force field. One of the partial charge models, IPolQ-Mod, is a fast continuum solvent-based implementation of the IPolQ approach. The AM1-BCC, RESP and IpolQ-Mod approaches all perform reasonably well (R2 > 0.8), while Vcharge, though faster, gives less accurate results (R2 of 0.5). The AM1-BCC results are more accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 54 publications
1
79
0
Order By: Relevance
“…This new parameter set outperforms our standard approach as represented by submission 004. Submission 544 applies standard AM1-BCC GAFF alchemical free energy calculations in GROMACS, and is nearly identical to submission 004 (but done independently in a different lab)[23]. It is worth briefly highlighting key metrics for these methods as well (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…This new parameter set outperforms our standard approach as represented by submission 004. Submission 544 applies standard AM1-BCC GAFF alchemical free energy calculations in GROMACS, and is nearly identical to submission 004 (but done independently in a different lab)[23]. It is worth briefly highlighting key metrics for these methods as well (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In computational chemistry, hydration free energies are of particular importance because they are frequently used in force field parameterization 2629 and in the testing of free energy methods and force fields. 1,814,3037 Furthermore, computed free energies are in some cases found to be accurate enough to highlight problems with experiments and assist in curation of experimental data. 13,38 …”
Section: Introductionmentioning
confidence: 95%
“…In this paper we focus on alchemical free energy calculations, which have been one of the most consistently reliable methods in recent applications such as the SAMPL series of challenges. 1,814,25 Consider a pair of end states A and B , and their respective Hamiltonians ℋ A ( q , p ; λ ) and ℋ B ( q , p ; λ ).…”
Section: Theory and Practical Aspects Of Alchemical Calculationsmentioning
confidence: 99%
“…These sets of charges are then averaged to take account of the electronic polarization of a solute molecule implicitly. Using this scheme, Muddana et al predicted the hydration free energies of the molecules in the SAMPL4 challenge with acceptable accuracy . Mecklenfeld et al also applied this kind of charges to calculate the solvation free energies of 29 drug‐like molecules in 12 diverse solvents and found that the overall performance of the physically motivated IPolQ‐Mod charges and the well‐calibrated restrained electrostatic potential (RESP) charges is similar …”
Section: Introductionmentioning
confidence: 99%